2020
DOI: 10.5604/01.3001.0014.3234
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Fixed Versus Adjustable Loop Cortical Suspension Devices in Arthroscopic Anterior Cruciate Ligament Reconstruction

Abstract: Background. Anterior cruciate ligament (ACL) reconstruction has remained the gold standard for ACL injuries, especially for young individuals and athletes exposed to high level sporting activities aiming to return to their preinjury level of activity. Cortical suspensory femoral fixation is commonly performed for graft fixation to the femur in anterior cruciate ligament reconstruction using hamstring tendons. The aim of this study was to compare the clinical results of using fixed and adjustable loop cortical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A total of 15 studies were included in this systematic review [ 1 , 3 5 , 9 , 11 , 14 , 25 , 28 , 31 , 33 , 34 , 36 , 41 , 43 ]. All studies were screened in full text.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 15 studies were included in this systematic review [ 1 , 3 5 , 9 , 11 , 14 , 25 , 28 , 31 , 33 , 34 , 36 , 41 , 43 ]. All studies were screened in full text.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies [ 4 , 5 , 43 ] included revision surgery in their outcome and two studies [ 28 , 34 ] reported on the number of patients undergoing revision surgery during the study period. Only the study by Asmussen et al [ 4 ] analysed the rate of revision surgery with an OR and found that ALDs had 0.51 (95% CI: 0.24–1.13) lower odds of having a revision surgery compared to FLDs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations